2017
DOI: 10.1155/2017/1478606
|View full text |Cite
|
Sign up to set email alerts
|

From Blood to Lesioned Brain: An In Vitro Study on Migration Mechanisms of Human Nasal Olfactory Stem Cells

Abstract: Stem cell-based therapies critically rely on selective cell migration toward pathological or injured areas. We previously demonstrated that human olfactory ectomesenchymal stem cells (OE-MSCs), derived from an adult olfactory lamina propria, migrate specifically toward an injured mouse hippocampus after transplantation in the cerebrospinal fluid and promote functional recoveries. However, the mechanisms controlling their recruitment and homing remain elusive. Using an in vitro model of blood-brain barrier (BBB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 80 publications
0
16
0
1
Order By: Relevance
“…In addition to trophic molecules, OEMSCs also secrete proteins related to the immune system. The two above-mentioned studies [23,45] reveal that inflammation associated molecules are observed in the secretome, notably several interleukins and members of the HLA complex. Overall, as described in two articles [21,46], OEMSCs exert immune-modulatory functions.…”
Section: Top Candidates Include Netrin 4 (Ntn4) Platelet Derived Gromentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to trophic molecules, OEMSCs also secrete proteins related to the immune system. The two above-mentioned studies [23,45] reveal that inflammation associated molecules are observed in the secretome, notably several interleukins and members of the HLA complex. Overall, as described in two articles [21,46], OEMSCs exert immune-modulatory functions.…”
Section: Top Candidates Include Netrin 4 (Ntn4) Platelet Derived Gromentioning
confidence: 99%
“…Among the putative underlying molecular mechanisms, we can cite the cytokines secreted by OEMSCs. Two independent studies, based on mass spectrometry, listed the content of OEMSC secretome [23,45]. The first one identified 274 proteins, of which 45 are known to be involved in cell growth, migration and differentiation [45]; the second listed 629 proteins, including 43 and 32 molecules associated to axonal guidance signaling and actin cytoskeleton signaling, respectively [23].…”
Section: Olfactory Stem Cells a Positive Add-on For Neglected Woundsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a rodent olfactory bulbectomy model, resident and infiltrating macrophages in the olfactory epithelium appeared to be the major producers of MCP-1 (21,45). MCP-1 is a chemotactic factor for not only monocytes/macrophages, based on a recent report, it can also stimulate migration of human olfactory ectomesenchymal stem cells derived from olfactory lamina propria (46). The role of MCP-1 in aging of the olfactory system is unclear.…”
Section: Mcp-1 Is a Key Chemokine That Regulates Migration And Infiltmentioning
confidence: 99%